2014
DOI: 10.1016/j.jamcollsurg.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients with Nonsurgically Managed Uncomplicated Appendicitis

Abstract: Background Emerging literature has supported the safety of non-operative management of uncomplicated appendicitis. Study Design Patients with emergent, uncomplicated appendicitis were identified by appropriate ICD-9 diagnosis codes in the California Office of Statewide Health Planning and Development (OSHPD) database from 1997 to 2008. Rates of treatment failure, recurrence, and perforation following non-surgical management were calculated. Factors associated with treatment failure, recurrence, and perforati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 21 publications
1
51
0
4
Order By: Relevance
“…One-year of follow-up data was included in two of these reports, and recurrence occurred in 13.3% (2 out of 15) and 10% (1 out of 10) of the patients [7,8]. According to meta-analyses of randomized, controlled trials in adults, nonoperative treatment for uncomplicated appendicitis is successful in 68-95% of patients and recurrence occurs in 4.4%-35% within 1 year [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-year of follow-up data was included in two of these reports, and recurrence occurred in 13.3% (2 out of 15) and 10% (1 out of 10) of the patients [7,8]. According to meta-analyses of randomized, controlled trials in adults, nonoperative treatment for uncomplicated appendicitis is successful in 68-95% of patients and recurrence occurs in 4.4%-35% within 1 year [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative treatment for uncomplicated appendicitis is now an accepted approach, and there are meta-analyses of randomized, controlled trials in adults [1][2][3][4][5][6]. However, there are few reports concerning nonoperative treatment for uncomplicated appendicitis in children [7][8][9].…”
mentioning
confidence: 99%
“…Options include surgical management with postoperative admission for observation, surgical management with same-day discharge after surgery, 7,8,10-13 and nonoperative management. [14][15][16][17][18][19] Although there is interest in treating acute appendicitis with antibiotics alone, the current data are unclear, and the standard of care remains appendectomy at this time. 16 Laparoscopic surgery has many advantages over open surgery; studies over time have consistently shown decreased length of stay, earlier tolerance of oral diet, and decreased pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2014 retrospective review of 231,678 patients with uncomplicated appendicitis, over 3 thousand of these patients were managed non-operatively; and of those patients, approximately 6% required appendectomy at that admission and 4.4% experienced recurrence of appendicitis after discharge during 7 year follow up. Of note, total charges were not statistically different between operative and non-operative patients, but length of stay was significantly longer in the non-operative group [146].…”
Section: Discussionmentioning
confidence: 75%